The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2002
DOI: 10.1152/ajpheart.00645.2001
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral microvascular changes in permeability and tight junctions induced by hypoxia-reoxygenation

Abstract: Mark, Karen S., and Thomas P. Davis. Cerebral microvascular changes in permeability and tight junctions induced by hypoxia-reoxygenation. Am J Physiol Heart Circ Physiol 282: H1485-H1494, 2002; 10.1152/ajpheart.00645.2001.-Cerebral microvessel endothelial cells that form the bloodbrain barrier (BBB) have tight junctions (TJ) that are critical for maintaining brain homeostasis and low permeability. Both integral (claudin-1 and occludin) and membrane-associated zonula occluden-1 and -2 (ZO-1 and ZO-2) proteins c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

29
277
0
3

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 339 publications
(309 citation statements)
references
References 63 publications
29
277
0
3
Order By: Relevance
“…Breakdown of BBB in tissue surrounding brain tumors occurs with concomitant loss of occludin expression (Papadopoulos et al, 2004). In vitro, hypoxia with reoxygenation altered occludin location and molecular weight, which correlated with the observed changes in cerebral microvascular permeability (Mark and Davis, 2002;Witt et al, 2003).…”
Section: Discussionmentioning
confidence: 88%
“…Breakdown of BBB in tissue surrounding brain tumors occurs with concomitant loss of occludin expression (Papadopoulos et al, 2004). In vitro, hypoxia with reoxygenation altered occludin location and molecular weight, which correlated with the observed changes in cerebral microvascular permeability (Mark and Davis, 2002;Witt et al, 2003).…”
Section: Discussionmentioning
confidence: 88%
“…Mark and Davis (2002) showed that hypoxia increases endothelial monolayer permeability, but expression of the TJ proteins ZO-1, ZO-2, and occludin changed little. The localization of these TJ proteins correlated with the permeability change.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it appears that the effects of MCP-1 on BBB permeability are caused by alterations in TJ complexes. Alterations in these complexes are implicated in BBB breakdown in many CNS pathological states including malaria, viral infection, multiple sclerosis, experimental allergic encephalitis, ischemia/reperfusion injury, and trauma (Brown et al, 1999;Mark and Davis 2002;Ng et al, 2003;Kirk et al, 2003). Furthermore, direct intracerebral injections of some proinflammatory cytokines (e.g., IL-1b, TNF-a, and IL-6), which are known to modify BBB, also cause structural changes in endothelial TJs (Bolton et al, 1998).…”
Section: Discussionmentioning
confidence: 99%